GOVERNING INTERNET GLOBALLY: A NECESSITY - Yani, Yanyan Mochamad; Djani, Dian Triansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
In the age of globalization, many questions were raised on the benefit and negative aspects of globalization and whether the world can manage globalization. The internet, as an important element of globalization, has contributed to many positive aspects of everyday lives but has also created discrimination, unevenness and has negative bearings on individuals as well as governments. Questions arise on the necessity of governing internet and the need to strike the right balance between ensuring that the negative impact of internet are properly managed through proper governance and the need to ensure that growth, creativity and preservation of rights that are needed in a globalized world continue unabated.